REGIONAL COMPETITIVENESS ANALYSIS AND ITS IMPLICATIONS FOR THE SPATIAL PLANNING OF LATGALE REGION - Ezmale, Sandra (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
This paper offers a contribution to contemporary studies of spatial planning. In particular, it focuses on the relationship between competitiveness and spatial planning. In the topical academic debates, there has been a growing interest in raising new paradigms to introduce innovative ways of undertaking long-lasting regional development problems. Territorial assets and spatial qualities have increasingly been regarded as factors for attracting on economic activities and increasing the competitiveness of regions. Spatial and non-spatial policies, planning documents, may have a significant role in enhancing the competitiveness of regions and territories by changing endogenous factors and producing shifts related to positioning and increasing the competitiveness of regions. This paper contains an analysis of competitiveness dimensions in the spatial planning documents of     Latgale planning region (Latvia) by focusing on a quantitative analysis of the specific dimensions of competitiveness.